Nuestra Señora de la Seguridad Nacional: ironía y comunidad en La aparición de la Virgen, de Enrique Lihn - Gonzalo Maier (Caravelle)
Through a close reading of Enrique Lihn’s La aparición de la Virgen (1987), this article discusses the use of irony as a tool to criticize media manipulation during the Chilean dictatorship. In particular, irony’s edge works on the alleged apparitions of the Virgin Mary, which, in the late 1980s, monopolized the attention of Chilean media. Besides, the use of irony also has a social function as it allows to reinforce a broken community which admits its lack of certainties and accepts the ambiguity of Lihn’s irony.